Sustainable debt - Gaetano Bloise; Heraklis M. Polemarchakis; Y. Vailakis (Theoretical Economics, 2021)
We show that debt is sustainable at a competitive equilibrium based solely on the reputation for repayment; that is, even without collateral or legal sanctions available to creditors. In an incomplete asset market, when the rate of interest falls recurrently below the rate of growth of the economy, self-insurance is more costly than borrowing, and repayments on loans are enforced by the implicit threat of loss of the risk-sharing advantages of debt contracts. Private debt credibly circulates as a form of inside money, and it is not valued as a speculative bubble. Competitive equilibria with self-enforcing debt exist under a suitable hypothesis of gains from trade.
Keywords: D52; F34; H63; 330; Rate of interest; self-enforcing debt; Ponzi games; incomplete markets; competitive equilibrium; gains from trade